2017
DOI: 10.1371/journal.pntd.0005818
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Toxocara species infection in the U.S.: Results from the National Health and Nutrition Examination Survey, 2011-2014

Abstract: Toxocariasis is one of the most common neglected infections of poverty in the U.S. with a reported National Health and Nutrition Examination Survey (NHANES) III (1988–1994) seroprevalence of 13.9% based on enzyme immunoassay testing. We reviewed NHANES data from 2011–2014 to assess current levels. Sera collected from NHANES 2011–2014 participants six years and older were tested for exposure using rTc-CTL-1 antigen, a more sensitive and specific recombinant antigen for IgG antibodies for Toxocara spp. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
1
28
0
3
Order By: Relevance
“…21 In another study in the USA, male gender, lower income, nonwhite ethnicity and less than collegelevel education were considered as associated risk factors for the Toxocara infection. 28 Fallah et al 23 for Toxocara infection with a significant difference between sex gender (more common in women), but not among the age groups. 29 Yet, a few studies reported that the seropositivity to Toxocara increases by age.…”
Section: A Few Examples Of Numerous Studies About the Seroprevalence Ofmentioning
confidence: 98%
“…21 In another study in the USA, male gender, lower income, nonwhite ethnicity and less than collegelevel education were considered as associated risk factors for the Toxocara infection. 28 Fallah et al 23 for Toxocara infection with a significant difference between sex gender (more common in women), but not among the age groups. 29 Yet, a few studies reported that the seropositivity to Toxocara increases by age.…”
Section: A Few Examples Of Numerous Studies About the Seroprevalence Ofmentioning
confidence: 98%
“…The other two are social insurance and taxation, both of which require a large formal economy ( 13 , 14 ). The 58th World Health Assembly focused on health care financing in order to promote access sharing risk and protecting poor people from impoverishment due to catastrophic health-care expenditures ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Source of zoonosis are the sick and infected animals that have direct contact with humans as well as animals which constitute a source of food for people [1][2][3][4][5][6][7][8][9][10][11][12]. The development of civilization does not always limit incidents of contagion with a disease, which could not be eliminated even in developed countries [14,[13][14][15][16][17][18][19][20]. Although there are effective ways to stop the spread of these diseases, they cannot always be used.…”
Section: Introductionmentioning
confidence: 99%